Evaluation of pushout bond strength of surface-treated glass fiber posts using universal adhesives with and without Silanization: an in vitro study - Chundi, Sai Vinitha; Praharshini, Yadapalli; Sampathi, Naga Lakshmi Reddy; Moosani, Gopi Krishna; Reddy, E Sujayeendranath; Meenakshi, Meher (International Journal of Dental Materials, 2024)
Background: Endodontically treated teeth that lack coronal tooth structure may require the placement of a post to provide adequate retention of a core foundation followed by a crown. Glass fiber posts have become one of the most popular because of the similar modulus of elasticity to dentin.Aim: To evaluate the push-out bond strength of surface-treated glass fiber posts to intraradicular dentin using universal adhesives with and without silanization. Materials and methods: Thirty single-rooted teeth were prepared up to the working length in a step-back technique and obturated. Post space was prepared to the length of 10 mm. Based on silanization specimens were divided into two groups of 15 each. Clearfil Tri-S bond universal was used as a bonding agent. The two groups including, Group 1 (without Silanization) (CTSBU):  post-treatment - only 9%HF, and Group 2 (With Silanization) (CTSBU+S): post-treatment - 9%HF followed by silane.  RelyxU200 was used to lute the posts, and the samples were divided into three parts (cervical, middle, and apical) and subjected to push-out bond strength analysis. Overall comparisons were done by analysis of variance (ANOVA), and pairwise comparisons were done by student t-test. The level of significance was set at p < 0.05 for all tests.Results: In all the root regions, group 2 (CTSBU+S) showed the highest pushout bond strength with statistical significance (p